2022
DOI: 10.3389/fonc.2022.858892
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Mechanism of microRNA-1224 in Human Cancer

Abstract: microRNAs (miRNAs) are a type of small endogenous non-coding RNAs composed of 20-22 nucleotides, which can regulate the expression of a gene by targeting 3’ untranslated region (3’-UTR) of mRNA. Many studies have reported that miRNAs are involved in the occurrence and progression of human diseases, including malignant tumors. miR-1224 plays significant roles in different tumors, including tumor proliferation, metastasis, invasion, angiogenesis, biological metabolism, and drug resistance. Mostly, it serves as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Since the discovery of miRNA functions in cancer, many miRNAs have been identified in various cancer types 8,13 . Furthermore, additional miRNAs have been found to be specifically dysregulated in different cancer types because of the discovery of novel miRNAs and the development of new detection technologies over the last decade [58][59][60][61] . For example, miR-34697, miR-45165, miR-638, and miR-152 have been identified to play a role in non-small cell lung cancer (NSCLC); miR-885-5p has been identified to play a role in kidney cancer; and miR-1285 has been identified to play a role in prostate cancer 58,62 .…”
Section: Mirnas As Biomarkers Of Cancer Diagnosis and Drug Efficacy P...mentioning
confidence: 99%
“…Since the discovery of miRNA functions in cancer, many miRNAs have been identified in various cancer types 8,13 . Furthermore, additional miRNAs have been found to be specifically dysregulated in different cancer types because of the discovery of novel miRNAs and the development of new detection technologies over the last decade [58][59][60][61] . For example, miR-34697, miR-45165, miR-638, and miR-152 have been identified to play a role in non-small cell lung cancer (NSCLC); miR-885-5p has been identified to play a role in kidney cancer; and miR-1285 has been identified to play a role in prostate cancer 58,62 .…”
Section: Mirnas As Biomarkers Of Cancer Diagnosis and Drug Efficacy P...mentioning
confidence: 99%
“…The tumor suppressor is effectively hindered by uncontrolled amplification of the miRNA gene that modulates it, which also induces carcinogenesis. Oncogenes or tumor-suppressor genes can function as miRNAs ( Ma M. et al, 2022 ). The initial miRNAs identified as silencers were miR-16a and miR-15o, which are expressed in site 13q14, and are present in more than 50% of those with chronic leukemia ( Braga et al, 2022 ).…”
Section: Role Of Mirna As Proto-oncogene and Oncogenementioning
confidence: 99%
“…At present, the involvement of miRNA from KSHV and host cells in the regulation of latent and lytic switches has received more and more attention ( Alomari and Totonchy, 2020 ; Kumar et al, 2022 ). miRNA is a class of small endogenous non-coding RNAs that can simultaneously regulate multiple target genes and play a unique tumor suppressive role in tumor occurrence, development, and metastasis through inhibition or degradation of the RNA translation ( Hussein et al, 2019 ; Liu et al, 2019 ; Ma et al, 2022 ). Wu et al (2022) reported that low-expressed miR-34a-5p in KSHV-infected cells could regulate the level of c-Fos and target the 3′-UTR region, thereby inhibiting cell proliferation and the expression of KSHV-related genes; thus miR-34a-5p may be used as a nucleic acid drug for the treatment of KSHV infection.…”
Section: Introductionmentioning
confidence: 99%